Inclusive Search for a Highly Boosted Higgs Boson Decaying to a Bottom Quark-Antiquark Pair - (:unkn) unknown (AMER PHYSICAL SOC, 2018)
An inclusive search for the standard model Higgs boson (H) produced with large transverse momentum (p(T)) and decaying to a bottom quark-antiquark pair (b (b) over bar) is performed using a data set of pp collisions at root s = 13 TeV collected with the CMS experiment at the LHC. The data sample corresponds to an integrated luminosity of 35.9 fb(-1). A highly Lorentz-boosted Higgs boson decaying to b (b) over bar is reconstructed as a single, large radius jet and is identified using jet substructure and dedicated b tagging techniques. The method is validated with Z -> b (b) over bar decays. The Z -> b (b) over bar process is observed for the first time in the single-jet topology with a local significance of 5.1 standard deviations (5.8 expected). For a Higgs boson mass of 125 GeV, an excess of events above the expected background is observed (expected) with a local significance of 1.5 (0.7) standard deviations. The measured cross section times branching fraction for production via gluon fusion of H -> b (b) over bar with p(T) > 450 GeV and in the pseudorapidity range -2.5 <eta< 2.5 is 74 +/- 48 (stat)(-10)(+17) (syst) fb, which is consistent within uncertainties with the standard model prediction.
Keywords: BROKEN SYMMETRIES; MASS